2021
DOI: 10.1039/d1nj03388c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures, DFT calculations, and catalytic application in the direct arylation of five-membered heteroarenes with aryl bromides of novel palladium-N-heterocyclic carbene PEPPSI-type complexes

Abstract: New series of Pd-catalysts based N-heterocyclic carbene ligand PEPPSI-Type, (PEPPSI = Pyridine Enhanced Precatalyst Preparation Stabilization and Initiation) with the general formula [Pd(II)Br2(NHC)(pyridine)]. were synthesized, and fully characterized by spectroscopic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
0
8
1
Order By: Relevance
“…The structures of palladium complexes were optimized using DFT with the B3LYP hybrid functional, by using a basis set of LanL2DZ, which is very common in palladium complexes calculations. Computations have been performed using the Gaussian 16 program package [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of palladium complexes were optimized using DFT with the B3LYP hybrid functional, by using a basis set of LanL2DZ, which is very common in palladium complexes calculations. Computations have been performed using the Gaussian 16 program package [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The electronic transitions were calculated by using time-dependent DFT(TD-DFT) with the B3LYP functional and the LanL2DZ basis set. In addition, the electronic spectra were calculated assuming water as a solvent using the CPCM method [ 31 ]. The orbitals and electronic spectra were visualized with GausView5.0.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors reported the TM‐catalyzed C5 direct arylation of furfural ( 1 ) as a particular case in a broader scope of heteroaromatic substrates [48–54] . For instance, in 2005, Fagnou and co‐workers reported one example of a direct arylation of 1 with one equivalent of phenyl bromide catalyzed by Pd(OH) 2 /C, leading to 75 % yield of a mixture 12 : 1 of the 2,5‐ and 2,3‐substitued isomers (Scheme 5a) [53] .…”
Section: Selective Functionalization Of Furfural Derivativesmentioning
confidence: 99%
“…The B3LYP 44 method was used to optimize all stable substances and intermediate molecules on the possible reaction path at the LanL2MB 45 calculation level. The geometric configurations of all stable substances and intermediates as shown in Figure 2 (see also the Supporting Information).…”
Section: Table 1 Carboxylation Of Imidazole With Co ...mentioning
confidence: 99%